A Mixed Methods Study of Pre-service Teachers’ Attitudes toward LGBTQ Themed Literature - Victor Malo-Juvera (Study and Scrutiny)
While many of studies provide valuable insights into teachers’ attitudes toward LGBTQ curricula, more research is needed that examines pre-service teachers’ attitudes toward LGBTQ themed texts.  The results from the type of research reported on in this article could assist teacher preparation programs to develop coursework intended to increase the willingness of pre-service teachers to use LGBTQ themed young adult literature in the classroom.